2008
DOI: 10.1007/s00401-008-0376-0
|View full text |Cite
|
Sign up to set email alerts
|

Copy number alterations of the polycomb gene BMI1 in gliomas

Abstract: Gliomas are heterogeneous tumours that grow in an uninhibited fashion, and these brain tumour cells share numerous characteristics with neural stem cells. The BMI1 gene encodes a component of the polycomb protein complex regulating epigenetically gene activity via histone modification. It functions for instance during the development of the central nervous system and maturation of neural cells. BMI-1 protein expression is deregulated in several forms of cancer and gene amplification has been identified in mant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 29 publications
2
31
0
Order By: Relevance
“…It has been shown that Bmi-1 is a key regulator of self-renewal in both normal and tumorigenic human solid tumor stem cells, including several types of brain cancer [10] and breast carcinoma [11] . Dovey et al [12] showed that Bmi-1 is over-expressed in numerous epithelial tumors and plays a key role in lung adenocarcinoma, thus providing a clue to lung cancer cell origin and lung tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that Bmi-1 is a key regulator of self-renewal in both normal and tumorigenic human solid tumor stem cells, including several types of brain cancer [10] and breast carcinoma [11] . Dovey et al [12] showed that Bmi-1 is over-expressed in numerous epithelial tumors and plays a key role in lung adenocarcinoma, thus providing a clue to lung cancer cell origin and lung tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to involvement of BMI1 in tumor progression, several reports have employed by Bruggeman et al [28], who concluded that BMI1 has been implicated in the pathogenesis of brain tumors such as gliomas. In addition Häyry et al [29], explored the genetic status and the correspondent expression patterns of BMI1 in a series of 100 low-and high-grade primary and recurrent gliomas suggesting that BMI1 possibly contributes to brain tumor pathogenesis. [30], concluded that increased expression of EZH2 in normal breast tissue disposes to subsequent development of cancer, also similar results by Zhang et al [24] , and Ahani et al [31].…”
Section: Bmi1 and Ezh2 Expression In Astrocytoma And Non-neoplastic Bmentioning
confidence: 99%
“…There are only a few studies that have analyzed the role of BMI-1 gene alterations in glioma in clinical samples (12,13). A DNA-RNA-protein analysis on the same sample could provide a complete picture in order to establish the mechanism of BMI-1 regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed BMI-1 gene alterations such as copy number variations (amplifications and deletions), and overexpression of mRNA and protein in different grades of gliomas (12,13,(27)(28)(29). showed that BMI-1 protein was overexpressed in the majority of grade 2-4 gliomas (12).…”
mentioning
confidence: 97%
See 1 more Smart Citation